Meaningful Learning Processes of Service Robots through Virtual Environments. - Guanopatin Claudio, Alex Vinicio (2024)
This paper presents a control scheme for navigation tasks of an aerial manipulator robot. The proposed controller prioritizes the kinematics of the sys tem considering its high redundancy, which is composed of an aerial platform and an anthropomorphic 3DOF robotic arm, the proposed control scheme is de coupled, i.e., a task is defined for the aerial robot and another task for the robotic arm. To validate the proposed controller, different tests will be performed in a virtual environment and in a partially structured environment. To perform the simulation tests, a virtual environment is developed to visualize the behavior of the manipulator robot, in the simulation environment tasks are planned in the workspace and adjust the controllers, avoiding damage to the physical robot. Once the controllers have been adjusted and simulated, experimental tests are carried out with the aerial manipulator robot.